Fenologia reprodutiva da pitaya vermelha em Jaboticabal, SP - Correia da Silva, Adriana de Castro (2015)
The dragon fruit (Hylocereus undatus) is recent crop cultivation in Brazil and there is still lack of studies to support the farmers. So, this research aimed to characterize the reproductive phenology of the crop in the region of Jaboticabal, Sao Paulo State, Brazil. It was evaluated red dragon fruit clones over two environmental conditions - under plastic screen black and white, with 50% of shady level, from March 2009 to December 2010. It was observed that the issuance of floral buds and the flowering on dragon fruit culture occurs with a combination of high temperatures and rainfall, with constant emission of floral buds from November to March while the flowering on dragon fruit culture occurs until mid-April. The color of plastic screen had influenced on amount of flowers. The time elapsed since the issuance of flower buds to anthesis is from 18 to 23 days, while the harvest occurs from 34 to 43 days after flower opening. At Jaboticabal, the time of appearance of flower bud to fruit harvest is from 52 to 66 days.